Anion gap as a prognostic index for cows with abomasal displacement and cecal dilatation and tortion - Kürşat TURGUT (Eurasian Journal of Veterinary Sciences)
Case records of total 66 cows with albomasal displacement and cecal dilatation and torsion were examined to determine whethar the preoperative heart rate, plasma base excess (BE) concentration, serum chloride (Cl-) and Anion gap (AG) could be used as a prognostic index. Cows were divided into groups according to the following ranges;